2009
DOI: 10.17705/1cais.02438
|View full text |Cite
|
Sign up to set email alerts
|

Global Diffusion of the Internet XV: Web 2.0 Technologies, Principles, and Applications: A Conceptual Framework from Technology Push and Demand Pull Perspective

Abstract: Web 2.0, the current Internet evolution, can be described by several key features of an expanded Web that is more interactive; allows easy social interactions through participation and collaboration from a variety of human sectors; responds more immediately to users' queries and needs; is easier to search; and provides a faster, smoother, realistic and engaging user search capability, often with automatic updates to users. The purpose of this study is threefold. First, the primary goal is to propose a conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 13 publications
0
34
0
4
Order By: Relevance
“…The web, its functions and adoption have fundamentally changed in the shift from Web 1.0 to Web 2.0. Arguably, the technology behind communication in Web 2.0 existed in the previous era (Kim et al ., ). Under Web 1.0, it was possible for messages to be sent on a one‐to‐one, one‐to‐many or many‐to‐many basis using email, discussion boards and instant messengers.…”
Section: Review Of the Literaturementioning
confidence: 97%
“…The web, its functions and adoption have fundamentally changed in the shift from Web 1.0 to Web 2.0. Arguably, the technology behind communication in Web 2.0 existed in the previous era (Kim et al ., ). Under Web 1.0, it was possible for messages to be sent on a one‐to‐one, one‐to‐many or many‐to‐many basis using email, discussion boards and instant messengers.…”
Section: Review Of the Literaturementioning
confidence: 97%
“…Year 2009 was the time when most organizations started using various Web_2.0 applications without clearly understanding what and how to embrace Web_2.0 applications (Kim et al, 2009). Most of the organizations created accounts on YouTube, Facebook, and Twitter only because many consumers and competitors were using these applications.…”
Section: Contributions and Implicationsmentioning
confidence: 99%
“…It soon elicited the attention of many businesses because of its capability to enhance the relationship between organizations and consumers (Andriole, 2010;Dorn et al, 2007). In short, Web_2.0 is a web application that assists people not only to post their opinions on websites, but to continue to interact and even collaborate with others on their topics of interest (Kim et al, 2009). Social network services, such as Facebook and Twitter, are good examples of such interaction-based applications; YouTube has also transformed its identity from a simple storage platform of numerous videos to a media channel that can specify target consumers with similar interests and perspectives (Berthon et al, 2012;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It does not coincide with any brand new or revolutionary technical innovation (Kim et al 2009), but instead uses a broad range of different technologies, applications, and functions for interactivity, networking, or user integration (Mrkwicka et al 2009). …”
mentioning
confidence: 99%
“…Cooke and Buckley (2008) viewed Web 2.0 as a set of tools that allows individuals to publish, share, and collaborate. Kim et al (2009) suggested participation, collaboration, rich user experience, social networking, semantics, and interactivity as characteristics of Web 2.0. Mrkwicka et al (2009) also viewed Web 2.0 as an enabling platform for user participation that focuses on philosophy of mutually maximizing collective intelligence, dynamic information sharing, and creation.…”
mentioning
confidence: 99%